2007
DOI: 10.1139/w07-002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with the mucopolysaccharide layers of three coral species affected and unaffected with dark spots disease

Abstract: Dark spots disease (DSD) is a relatively new coral disease that has become one of the most prevalent afflictions in the Caribbean Sea. To partially characterize bacterial communities associated with DSD, carbon utilization patterns of bacterial strains isolated from the surface mucopolysaccharide layers of healthy and DSD-affected Montastraea annularis, Montastraea faveolata, and Siderastrea siderea were compared with each other and with bacterial strains isolated from the water column by using cluster analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Other coral diseases in the Caribbean, such as White Band Disease type II, Yellow Blotch/Band and Dark Spots Disease, were found to be associated with elevated Vibrio spp . prevalence [ 4 ], [54]–[ 56 ], suggesting the involvement of Vibrio strains in numerous coral diseases including coral bleaching [ 5 ], [57]–[ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other coral diseases in the Caribbean, such as White Band Disease type II, Yellow Blotch/Band and Dark Spots Disease, were found to be associated with elevated Vibrio spp . prevalence [ 4 ], [54]–[ 56 ], suggesting the involvement of Vibrio strains in numerous coral diseases including coral bleaching [ 5 ], [57]–[ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the composition of bacterial communities may suggest that disease agents impair the structure of natural bacterial communities. It is likely that compromised or dead tissues represent a “micro-niche” that can be colonised by more competitive and opportunistic bacteria in the surrounding water and sediments or transmitted by other marine organisms [14], [15], [17], [18], [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, [7] suggested that the disease may in fact affect many other species of coral further highlighting the importance of this syndrome in coral ecology and population biology. Interestingly, [5] highlighted significant differences in the morphology of the circular spots associated with these different coral species, and suggested that DSS might actually encompass more than one disease showing similar signs [1], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The exposed skeleton subsequently gets colonised by algae and/or boring sponges [12]. Although the visual signs of DSS can be seen on most Caribbean reefs, the aetiology of DSS, like many other coral diseases, still remains unknown and only a few studies have attempted to identify a specific pathogen; nonetheless both fungi [13] and bacteria [9] have been implied as potential causal agents to date. Characteristically, the Symbiodinium found in DSS lesions are swollen and darker in pigment in comparison to their natural healthy state with changes observed in their mitotic indices [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation